Professional sports teams: going beyond the core. Issue 4 (4th November 2019) - Pritchard, Adrian; Cook, David; Jones, Andrew; Bason, Tom; Salisbury, Paul; Hickman, Ellie
Abstract : Purpose: The addition of products to the core of matches by professional sports teams (PSTs) has received much coverage. However, there has been limited work as to how their stadiums are used to stage non-sporting events. The purpose of this paper is to investigate how clubs in the English Football League (EFL) use their venues to diversify into other markets. Design/methodology/approach: Secondary sources were used to categorise the teams who played in the EFL by: average division turnover, stadium capacity and stadium age. Semi-structured interviews were held with a member of the commercial teams of 21 clubs. Findings: Clubs use their stadiums to supply a range of products and working with partners is commonplace. These products are targeted at a range of stakeholders, such as supporters, the local community and regionally based organisations. In addition to their own efforts, increased geographical coverage for clubs usually develops in three ways: via internal marketing by local organisations who use the facilities, agents who market the stadium for the club and the EFL who market the league/clubs holistically. Research limitations/implications: The use of a stadium allows PSTs to diversify by providing new products for new markets. In this instance it has led to the development of capabilities in areas such as conferencing, funerals and weddings. Originality/value: This is one of the first papers to examine the capabilities developed by PSTs that lie outside the staging of matches.